Gender differences in physical activity and sedentary behavior of Japanese primary school children during school cleaning time, morning recess and lunch recess - Chiaki Tanaka; Maki Tanaka; Shigeru Inoue; Masayuki Okuda; Shigeho Tanaka (BMC, 2019)
Abstract Background The school environment provides crucial opportunities for children to engage in health-promoting physical activity (PA). Japanese children clean their schools and have recess time every school day. The primary aim of the study is to describe the levels of physical activity during school cleaning and recess time while comparing it between genders. Methods PA and sedentary behavior (SB) of 230 boys and 252 girls aged 6-12 years-old from 14 public primary schools were assessed for 7 consecutive days with a triaxial accelerometer. Minutes of SB, and moderate-to-vigorous PA (MVPA) as a percentage in each of school cleaning time (15 min/day: 58% of the 14 schools or 20 min/day), morning recess time (15 min/day: 6% or 20 min/day) or lunch recess time (15 min/day: 29%, 20 min/day: 47% or 25 min/day) were evaluated. A one-way analysis of variance or Student's t test was used to examine differences in %PAs and %SB between school cleaning time and morning and lunch recess time, and between genders. Results In a school day, the percentage of total daily MVPA during school cleaning time, morning recess and lunch recess time was 19.4 ± 6.8% (15.2 ± 5.3 min/day) for boys and 16.9 ± 5.8% (10.5 ± 4.3 min/day) for girls. For boys, the proportions of MVPA in morning and lunch recesses and SB during the morning recess were significantly higher than during school cleaning time (p < 0.001). For girls, similar results were obtained and the SB during lunch recess was also higher than during school cleaning time (p < 0.001). Conclusions These findings suggest that the total amount of school cleaning time, recess and lunch time likely contribute to daily MVPA but the beneficial effects should be further explored in future intervention studies.